Marco Polo - Rich, Richard; Brown, Jared F.; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Entertainment, 2005)
An animated biography of Marco Polo. Shows a life of this Venetian explorer focusing on the highlights of his travels to India, China and other many exotic lands in the thirteenth-century.
"Premium website accessible through DVD-ROM"--Container.
"NEST complete learning system."
DVD ; Dolby Digital 2-channel surround sound.
Includes Spanish language track with optional English or Spanish subtitles.
89679
Keywords: Polo, Marco, -- 1254-1323? -- Juvenile films; Explorers -- Italy -- Biography -- Juvenile films; Animated films